Vitamin D Receptor, Retinoid X Receptor, Ki-67, Survivin, and Ezrin Expression in Canine Osteosarcoma - John Davies; Heather Heeb; Rama Garimella; Kimberly Templeton; David Pinson; Ossama Tawfik (Veterinary Medicine International)
Canine osteosarcoma (OS) is an aggressive malignant bone tumor. Prognosis is primarily determined by clinical parameters. Vitamin D has been postulated as a novel therapeutic option for many malignancies. Upon activation, vitamin D receptors (VDRs) combine with retinoid receptor (RXR) forming a heterodimer initiating a cascade of events. Vitamin D's antineoplastic activity and its mechanism of action in OS remain to be clearly established. Expression of VDR, RXR, Ki-67, survivin, and ezrin was studied in 33 archived, canine OS specimens. VDR, RXR, survivin, and ezrin were expressed in the majority of cases. There was no statistically significant difference in VDR expression in relationship with tumor grade, type, or locations or animal breed, age, and/or sex. No significant association (p=0.316) between tumor grade and Ki-67 expression was found; in particular, no difference in Ki-67 expression between grades 2 and 3 OSs was found, while a negative correlation was noted between Ki-67 and VDR expression (ρ=−0.466), a positive correlation between survivin and RXR expression was found (p=0.374). A significant relationship exists between VDR and RXR expression in OSs and proliferative/apoptosis markers. These results establish a foundation for elucidating mechanisms by which vitamin D induces antineoplastic activity in OS.